PIG HUSBANDRY PRACTICES AT KYRDEM VILLAGE IN RI-BHOI DISTRICT OF MEGHALAYA (Indian Journal of Animal Production and Management, 2014)
The study was carried out at Kyrdem village in Ri-Bhoi district of Meghalaya. The study revealed that, 72% farmers reared the pigs in confinement area with raised platform constructed with woods and bamboos. The farmers in Kyrdem village rear crossbred pigs and all the farmers in the village followed natural breeding. The average litter size at birth was six while the litter size at weaning five. All the farmers followed stall feeding and supplied kitchen waste with some locally available weeds after boiling and 80 percent pigs were offered concentrate. The farmers provided feeds twice daily in morning and evening. The farmers (20%) followed deworming using either traditional or allopathic medicine. However, 72 percent of the farmers vaccinated the pigs against swine fever. Similarly, only 8 percent of the farmers treated their piglets against piglet anaemia with iron injection and 28 percent of them used ectoparasitic drugs in their farms. The farmers followed weaning and castration of their piglets. Only 68 percent of the farmers paid special attention to their pregnant sows and 80 percent of them took special care of sows after farrowing. 64 % of the farmers clean the sty once in two days. Pigs were marketed at the age of one year or above when they attained the body weight of 70-80 kg or more.
Keywords: Survey; pigs; litter size; weaning; health care; sty; castration; market